Characterization of a Functionally Gradient Ceramic Based on CaZrO3 – MgO - Babo, Débora Rafaela Telha de (2018)
In the case, where the structure is exposed to severe conditions of operation, such as high strength, wear and high-temperature gradients (e.g. engine components, insulation system, thermal barrier and thermal shield) must be applied. In this work, it was developed and characterized a functional gradient ceramic coating. A ceramic composite based in CaZrO3 – MgO was used in order to design a material with successive layers of molar composition 2:3, 1:1 and 1:3 of CaZrO3:MgO, respectively. A dense material was obtained by sintering assisted reaction (Figure 1). Thermal conductivity at room temperature, hardness, fracture toughness, surface energy, and microstructure were characterized.The results show for monolithic specimens of 2:3 CZ, 1:1 CZ and 1:3 CZ a H of 9,9 GPa, 9,8 GPa and 10,1GPa; a Kc of 1,6 MPa.m1/2, 1,7 MPa.m1/ and 2,1 MPa.m1/2; a k of 0,59 W/mK; 0,76 W/mK and 0,79 W/mK; and a surface energy (SE) of 43,27 mN/m, 51,39 mN/m and 46,55 mN/m, respectively. The functional gradient ceramic shows a H of 10,7 GPa, a Kc of 1,97 MPa.m1/2; a k of 0,82 W/mK and SE of 53,98 mN/m. The individual composition and the functional gradient ceramic show a similar relative density of 4,3 g/cm3 and a porosity of 0,2%. This design methodology has the advantage of allowing the properties of the same material to suit different substrates.